2013
DOI: 10.1177/0883073813488828
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Interferon Beta-1a in Pediatric Multiple Sclerosis

Abstract: To expand current knowledge, we examined the safety and tolerability of subcutaneous interferon β-1a in patients with pediatric-onset multiple sclerosis. Records from 307 patients who had received at least 1 injection of subcutaneous interferon β-1a for demyelinating events when aged younger than 18 years were reviewed. Overall, 168 (54.7%) patients had at least 1 prespecified medical event related to or under close monitoring with subcutaneous interferon β-1a or specific to pediatric patients, 184 (59.9%) had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
45
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 33 publications
3
45
0
3
Order By: Relevance
“…Based on the results from a recently published study by Tenembaum et al, 22 the label of IFNb-1a 22 or 44 mg has been modified in the European Union as follows: "The results of this study suggest that the safety profile in children (2-11 years old) and in adolescents (12-17 years old) receiving Rebif 22 or 44 mg subcutaneous 3 times per week is similar to that seen in adults. The safety and efficacy of Rebif in children below 2 years of age have not yet been established.…”
Section: Results In Young Children Vs Adolescentsmentioning
confidence: 93%
See 4 more Smart Citations
“…Based on the results from a recently published study by Tenembaum et al, 22 the label of IFNb-1a 22 or 44 mg has been modified in the European Union as follows: "The results of this study suggest that the safety profile in children (2-11 years old) and in adolescents (12-17 years old) receiving Rebif 22 or 44 mg subcutaneous 3 times per week is similar to that seen in adults. The safety and efficacy of Rebif in children below 2 years of age have not yet been established.…”
Section: Results In Young Children Vs Adolescentsmentioning
confidence: 93%
“…1,3 The European document suggested early use of DMTs to prevent relapses, accumulation of disability, and accumulation of brain damage, recommending careful clinical and MRI follow-up. 3 Similarly, the International Pediatric Multiple Sclerosis Study Group consensus statement Table 1 Demographic and clinical findings of studies a evaluating the results of interferon-b (IFN-b) and glatiramer acetate in pediatric patients with multiple sclerosis Waubant et al 16 Mikaeloff et al 17 Ghezzi et al 21 Pohl et al 19 Tenembaum and Segura 20 Ghezzi et al 21 Tenembaum et al 22 Banwell et al 23 Mikaeloff et al 24 Kornek et al 25 Ghezzi et al 21 Drug The general approach is shown in the figure.…”
Section: Results In Young Children Vs Adolescentsmentioning
confidence: 99%
See 3 more Smart Citations